Ronan Paddison: reflections on a supervisor, mentor, friend. Issue 2 (3rd May 2020) - Beel, David; Crotty, John; Docherty, Iain; McCormick, Jim; Rae, Norman; Stewart, Derek
ABSTRACT: This is a composite paper bringing together six personal reflections on being supervised as doctoral students by Ronan Paddison. It contributes insightful and poignant voices of experience to a special issue commemorating the academic contributions – here with wider implications beyond the immediately 'academic' – of Ronan Paddison (1945–2019), the founder and for many years Editor-in-Chief of this journal, Space and Polity . The six sets of reflections have been authored independently of one another, but their cumulative effect is to demonstrate the depth of 'hidden' academic (and related) contribution made by Ronan to nurturing early career academics formally (through the doctoral supervision process) and more informally (in numerous ways and sometimes continuing well beyond the submission and award of a thesis). ( Editorial abstract )